The Rise of Robinson Mall in Valencia City Bukidnon: Breaking Barriers of Urbanization - Dominador A. Dayson Jr; Roland A. Tacan; Princes Luise D. Picaza (International Journal of Economic, Finance and Business Statistics, 2023)
Urbanization refers to general increase in population and the amount of industrialization of a settlement. It symbolizes the movement of people from rural to urban areas. Urbanization happens because of the increase in the extent and density of urban areas. Due to uncontrolled urbanization in Valencia City Bukidnon, environmental degradation has been occurring very rapidly and causing many problems like land insecurity, worsening water quality, excessive air pollution, noise and the problems of waste disposal. This paper emphasizes on the effect of urbanization on environmental components mainly public health and habitat, climate, biosphere, land and water resources. A case study of urbanization in Valencia City has been carried out leading to conclude on the existing.